Analysis of Linear Equating of Senior School Certificate Multiple-Choice Examination Papers in Economics - Dorcas Sola Daramola; Adekunle Thomas Olutola; Mohammed Idris Jimoh (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2022)
Background: Test equating methods are statistical tools used to produce exchangeable scores across different test forms. However, people believe that it is impossible to develop multiple forms of tests that have the same psychometric properties. Contribution: The study therefore analyzed the linear equating of senior school certificate multiple-choice examination papers in Economics. Method: A Non-equivalent Groups Anchor Test (NEAT) design was adopted for the study. The sample for the study consisted of 1,119 senior secondary three students. The 2009 WAEC, NECO, and NABTEB SSCE multiple-choice Economics papers were adapted and used for data collection with 0.67, 0.64, and 0.60 coefficients of content validity as well as 0.79, 0.76, and 0.70 reliability coefficients. Data collected were analyzed using descriptive statistics, T-scores, and Analysis of Variance.  Results: Findings revealed that there was no difference in examinees’ ability, thus equating process could take place. The finding also revealed an F-value of 1.953, which was not significant at the 0.05 alpha level since the p-value (0.142) was greater than 0.05. It showed a score of 41 in WAEC and NECO was equivalent to 42 in NABTEB. It also showed a score of 45 in WAEC was equivalent to 46 and 50 in NECO and NABTEB respectively. Conclusion: The researchers therefore concluded that the 2009 WAEC and NECO SSCE Economics multiple-choice items tended to be equivalent while that of NABTEB was different. It was recommended among others that a regulatory body could be established to monitor and standardize these examinations conducted in Nigeria